THE TRANSFORMATION OF EDUCATION IN THE DIGITAL ERA FOR ARABIC LANGUAGE LEARNING: WITH DISTANCE LEARNING - Baroroh, Latifatul (Kitaba, 2025)
The digital era has revolutionized education, paving the way for innovations such as distance learning. This study examines the transformative impact of digital technology on education, emphasizing its potential to enhance accessibility, flexibility, and inclusivity in learning. Key findings reveal that distance learning effectively bridges geographical barriers, providing equitable educational opportunities for diverse learners. Additionally, the integration of digital tools fosters personalized learning experiences, promoting self-paced progress and interactive engagement. However, challenges such as gaps in digital infrastructure, limited technological literacy, and the need for educators to adapt to digital pedagogies remain significant. To address these issues, this research recommends prioritizing investments in digital infrastructure, offering comprehensive training for educators, and developing learner-centered digital content. The findings underscore that when supported by robust strategies, distance learning not only modernizes education but also equips learners with 21st-century skills, including critical thinking, collaboration, and technological proficiency. By embracing these changes, education systems worldwide can transition toward a more equitable and sustainable future. This study concludes that distance learning is not merely a response to technological advancements but a pivotal step in reimagining education for the digital age.